Localizing Islam in Europe : Turkish Islamic communities in Germany and the Netherlands - Yükleyen, Ahmet (Religion and politics., 2011)
Yükleyen compares five different forms of religious communities among Muslim immigrants in the Netherlands and Germany that represent a spectrum from moderate to revolutionary Islamic opinions. Drawing on extensive fieldwork, he finds that, despite differences in goals and beliefs, these communities play an intermediary role, negotiating between the social and religious needs of Muslims and the socioeconomic, legal, and political context of Europe. Yükleyen's rich ethnography shows that there is no single form of assimilated and privatized "European Islam" but rather Islamic communities and their interpretations and practices that localize Islam in Europe.